Methodological training of future teachers through the implementation of didactic-methodological complexes - Upatova, I. P. (Problems of Engineer-Pedagogical Education, 2018)
The process of rebuilding the structure and content of secondary education in modern conditions arouses a contradiction between the educational needs of secondary schools and teacher training in higher educational institutions. The article substantiates the expediency of implementing didactic complexes aimed at promoting the development of methodological competence of future teachers. The study is based on a series of methods: observation, pedagogical experiment, analysis, generalization, the experimental group included second-year students. The purpose of the article is to disclose the content and conditions for successful implementation of didactic-methodological complexes in the process of methodological training of school teachers. The introduction of didactic-methodological complexes results in finding ways that will ensure high-quality methodological training of teachers, which will ultimately lead to the acceleration of their development as specialists in methodology. The implementation of didactic guidance systems encourages future primary school teachers to think critically about their own methodological activity and helps to acquire methodological competence. Further research into the elaboration of methodological approaches to methodological training of future teachers is envisaged.